Hadid : Zaha Hadid complete works, 1979-2013 - Jodidio, Philip (Taschen, 2013)
Zaha Hadid is a wildly controversial architect whose work remained largely unbuilt for years despite awards and critical acclaim. Yet she has completed numerous structures like the Glasgow Riverside Museum and the Rosenthal Center for Contemporary Art in Cincinatti, and she now ranks among the elite of world architecture.--